ANALYSIS OF THE PERFORMANCE OF CREATIVE BUSINESSES IN THE DIGITAL AGE TO ENHANCE REGIONAL ECONOMIC GROWTH - Lusaputra, Fadhil Ghani; Rudianti, Walid (STIE Pelita Nusantara Semarang, 2025)
Creative business performance is not only measured by financial gain, but also by the ability to innovate, customer satisfaction, and business sustainability. In this age of digitalization, using digital technology is crucial for facing new challenges and opportunities. This research examines the role of government policy, access to capital, social networks, and creative business performance in driving regional economic growth, with a case study in Banjarnegara Regency. To enhance the accuracy of the findings, this study employs a qualitative methodology, cross-referencing information, including observation, interviews, focus group discussions, and existing documents. The informants consisted of nine creative business owners and related government officials. The results show that, to date, there is no specific local government policy regulating creative economic activities in Banjarnegara. Access to financing information is still limited, so a strategy is needed to expand capital opportunities for creative business owners. However, social networks among business owners are quite good, as evidenced by the formation of communities and business groups according to their respective fields. The performance of creative businesses is considered positive because the owners have the ideas, concepts, and skills to develop their businesses. This is reflected in the increasing number of creative business owners in Banjarnegara. In conclusion, strengthening government policies and access to capital is necessary to reinforce the creative business ecosystem, which already has good social networks and performance, so that it can contribute optimally to regional economic growth.